Numerical Simulation of Hot Closed Die Forging of a Low Carbon Steel Coupled with Microstructure Evolution - A. L. I. Moraes; O. Balancin (Materials Research, 2015)
Hot closed die forging is a regular process applied to manufacture metallic components used in supporting and fixing cable conductors in electric power transmission lines. In this forming process, the final microstructure of the workpiece depends on the control of several processing parameters. In this study, simulation of the industrial forging process of a ball hook component was performed using the finite element software DEFORM-3D following the thermomechanical procedures coupled with microstructure evolution. This simulation allowed the study of the process parameters such as temperature, strain and strain rate and microstructure evolution during hot closed die forging of a low carbon steel. The geometry and grain size evolutions obtained by simulation are compared with those found in the actual process and measured by optical microscopy. The attained data indicated that the simulation is able to describe processing parameters and microstructure evaluation during hot forging of a metallic component.